Analysis of Marketing Opportunity Increase based on Consumer Criteria for Hydroponic Vegetable Producers in Surabaya - Titik Yuliarini; Soeharsono Soeharsono; Mirni Lamid; Mohammad Anam Al Arif; Sarmanu Sarmanu; Sri Hidanah (Universitas Sebelas Maret, 2020)
Consumer is one of the influential factors in marketing. The study was conducted to analyze the increase in marketing opportunities based on consumer criteria for hydroponic vegetable producers in Surabaya. The research was carried out in Surabaya from Mei to June 2018. This type of research is observational analysis with survey methods on three producers about the relationship between producers and consumers according to their respective producers. Data were analyzed with AHP (Analysis Hierarchy Process) and the process used Expert Choice 2000. Data were examined using descriptive or qualitative analysis and quantitative analysis. Quantitative analysis includes a scale of trust and commitment measurement. The distribution of hydroponics vegetables at “Kebunsayur Surabaya” prioritizes ‘restaurant’ and ‘hotel’, “JawaRa Farm” prioritizes ‘kale suppliers’ and “One STOP Hydroponics” prioritizes ‘individual customers’ (vegetable displays).